(untitled) (Fiep Bulletin - online, 2013)
This study compared percentage body fat and nutritional status in a group of men and women 20 to 80 years of age living in Vale do Sinos, southern Brazil. This descriptive study enrolled a convenience sample of 1004 participants (323 men) divided into five age groups. Nutritional status was analyzed according to body mass index. Percentage body fat was measured using a skinfold caliper and the equations described by Jackson & Pollock and Williams. Other anthropometric measures were: total body mass and height, measured with a balance beam scale and a height rod. ANOVA and the Tukey test were used to analyze the differences between percentage body fat and nutritional status. The Student t test was used to compare actual and recommended means according to gender. The comparison of mean percentage body fat and nutritional status categories revealed statistical differences (p<0.05), which suggested that participants had pre-obesity characteristics. A significant difference (p<0.05) was found in the analysis of mean percentage body fat in all nutritional categories in the group of women, which indicated that percentage body fat in the group of women was above recommended normal values. Women in the “underweight” and “normal-weight” categories did not show any significant differences in percentage body fat, but a significant difference was found for men 30 to 39 years and over 60 years of age. These results are more concerning for women because of their greater prevalence of percentage body fat, but this type of fat distribution is associated with metabolic disorders and cardiovascular diseases in both men and women.